Keseimbangan antara Profesionalitas dan Kesejahteraan Guru Bahasa Arab dalam Perspektif Maqasidi Qur'ani - Abas, Abu (Study Program of Arabic Language Teaching, 2024)
This research on language education policy aims to formulate language education policies regarding the inequality between professionalism and teacher welfare from the perspective of Qur'anic maqasidi. The research method used in this policy article is qualitative, with a literature study approach. Policy article data is in the form of policy choices from the perspective of Quranic maqasidi, obtained from various sources of articles, the Quran, applicable regulations, scientific journals, and books. The data collection technique is carried out by documentation. The data analysis was done using data reduction, presentation, and conclusion. The research on language education policy results stated that 21 verses of the Qur'an were reduced into four types of